2018
DOI: 10.30673/sja.69997
|View full text |Cite
|
Sign up to set email alerts
|

Miten Raja-Karjalan murre eroaa suomesta?

Abstract: Tutkimuksessa tarkastellaan kuuntelutestimenetelmää käyttäen ei-lingvistien havaintoja karjalan kielestä. Kohderyhmänä on 31 rajakarjalaistaustaista pohjoiskarjalaista, jotka edustavat karjalankielisiä siirtokarjalaisia tai heidän jälkeläisiään. He ovat syntyneet v. 1917–1969, ja heidän sukunsa ovat olleet kotoisin Ilomantsin itäkylistä, Suojärveltä, Suistamolta, Impilahdelta tai Salmista. Testissä he kuuntelivat lyhyen eteläkarjalaismurteen näytteen, josta heidän tehtävänään oli arvioida, miltä osin näytteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…This, however, is understandable because working methods and tools have changed during recent decades. Overall, our findings are in line with earlier research among the descendants of Border Karelians in Finland, which showed that the respondents had good recollections of the Karelian they had heard during their childhood and reported having a rather good passive command of Karelian (Palander & Riionheimo 2018a, 2018b).…”
Section: Tver’ Karelians’ Conceptions Of Their Own Dialectsupporting
confidence: 91%
See 1 more Smart Citation
“…This, however, is understandable because working methods and tools have changed during recent decades. Overall, our findings are in line with earlier research among the descendants of Border Karelians in Finland, which showed that the respondents had good recollections of the Karelian they had heard during their childhood and reported having a rather good passive command of Karelian (Palander & Riionheimo 2018a, 2018b).…”
Section: Tver’ Karelians’ Conceptions Of Their Own Dialectsupporting
confidence: 91%
“…Research into Karelian has made use of folk linguistic methods but applied and adjusted them to fit this particular linguistic context. Previous research has focused on what Finns with and without Karelian roots mean by the term Karelian, what linguistic features they assign to Karelian, and how they recognise samples of Karelian (Palander 2015;Riionheimo & Palander 2017, 2020Palander & Riionheimo 2018a, 2018b. Furthermore, there are a few studies concerning the language regard of North (Viena) Karelians living in Russia, how they value the Karelian dialects in relation to each other and to the Finnish and Russian languages (Kunnas 2013), and how the North Karelians recognise different varieties of Karelian (Kunnas 2018).…”
Section: Theoretical and Methodological Backgroundmentioning
confidence: 99%
“…This proves the well-known fact that national borders can and often do serve to isolate speech communities (e.g. Palander, Riionheimo & Koivisto 2018).…”
Section: The Kvens Writing In Isolation In a Multilingual Environmentsupporting
confidence: 59%